The involvement of non-governmental organisations in achieving health system goals based on the WHO six building blocks: A scoping review on global evidence - Leila Doshmangir; Arman Sanadghol; Edris Kakemam; Reza Majdzadeh (PLoS ONE, 2025)
Background Non-governmental organisations (NGOs) have the potential to make a significant contribution to improving health system goals through the provision of resources, health services and community participation. Therefore, this paper examines the role of NGOs in achieving health system goals, based on the six building blocks of a health system framework, and identifies strategies to enhance NGO involvement in achieving health system goals. Methods A scoping systematic review methodology was used to map and synthesise the existing literature on the topic, following the latest JBI six-stage framework. Four databases and one search engine including PubMed, Web of Science (ISI), EMBASE, Scopus and Google Scholar were searched from January 2000 to January 2024. The results were synthesised using a directed content analysis approach, and the findings were categorised according to the dimensions of the six building blocks. Results NGO involvement in health system goals can effectively address gaps in service delivery, strengthen the health workforce, improve health information systems, increase access to essential medicines, mobilise resources and promote good governance. In addition, six key strategies were identified, including joint planning, policy development, capacity building, resource allocation, developing collaboration, and improving the quality of health care, to enhance NGO participation in achieving health system goals. Conclusion NGOs can play a critical role in achieving health system goals, alongside government and other key health stakeholders. Governments need to use evidence-based policies and interventions to support NGOs to realise their potential in achieving health system goals.